Women still at work : professionals over sixty and on the job - Fideler, Elizabeth F. (Rowman & Littlefield Publishers, 2012)
The fastest growing segment of the workforce is women age sixty-five and older. Women Still at Work draws on national survey data and in-depth interviews to show the many reasons why women are working well past the traditional retirement age. The book is filled with profiles of real working women, with a focus on women in the professional workforce.